Silicon-oxygen bond-containing sulfonate additive, electrolyte and electrochemical device

By using silicon-oxygen bond-containing sulfonate additives in the electrolyte of lithium-ion batteries, the challenges of high-temperature cycling and safety of lithium-ion batteries are solved, achieving higher battery stability and safety while reducing high-risk Dosage of carcinogens.

CN119361819AInactive Publication Date: 2025-01-24ANQING CHAOREN ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411180664.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have challenges in high temperature cycles and safety, especially due to the high risk of carcinogenicity and safety risks of the use of 1,3-propane sulfonate.

Method used

Using silicon-oxygen bond-containing sulfonate additives, this additive has higher stability and safety, can form a stable membrane structure in the electrolyte, inhibit the decomposition of the electrolyte, reduce gas production, and improve the high-temperature cycle performance of the battery .

Benefits of technology

By using silicon-containing sulfonate additives, the safety risk of the battery is significantly reduced, and the battery internal resistance and cycle performance of the battery under high temperature cycle conditions is improved, and the amount of lactopatate of 1,3-propylene sulfonate is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005012052530000021
    Figure BDA0005012052530000021
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytes, and discloses a sulfonate additive containing a silicon-oxygen bond, an electrolyte and an electrochemical device, the additive is a sulfonate organic compound containing the silicon-oxygen bond, the additive is added into the electrolyte, the gas production effect of battery formation can be inhibited, and the high-temperature cycle performance of a battery can be improved. According to the sulfonate additive containing the silicon-oxygen bond, the use amount of a high-risk substance 1, 3-propane sultone in an electrolyte can be reduced, the use amount of the 1, 3-propane sultone can be remarkably reduced on the premise that the formation gas production effect and the high-temperature cycle performance of a battery are not remarkably changed, and the use amount of the 1, 3-propane sultone can be remarkably reduced on the premise that the high-temperature cycle performance of the battery is remarkably improved. The 1, 3-propane sultone belongs to a high-risk cancerogenic substance, and the safety risk of the battery can be remarkably reduced by reducing the dosage of the 1, 3-propane sultone in the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytes, and in particular to a silicon-oxygen bond-containing sulfonate additive, an electrolyte and an electrochemical device. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, long cycle life, high specific energy density and low environmental pollution. Therefore, they are currently the most promising and green secondary batteries. Lithium batteries are mainly composed of positive electrodes, negative electrodes, electrolytes and separators. As the key material for these two types of batteries, electrolytes mainly play the role of transmitting lithium / sodium ions during the charging and discharging process. Their role and importance to batteries are like blood to the human body. The essence of chemical energy storage devices is the oxidation / reduction reaction at the electrode interface to achieve the conversion between chemical energy and other forms of energy. The oxidation / reduction reaction at the electrode interface is the transfer of electrons at the interface between the ionic conductor phase and the electronic conductor phase. The electrons entering the electronic conductor phase are reduction reactions, and the electrons entering the ionic conductor phase are oxidation reactions. In this process, the components in the electrolyte inevitably undergo oxidation / reduction reactions, which ultimately lead to battery failure.

[0003] As one of the important means to improve the stability of lithium-ion batteries, the improvement of the electrode interface of lithium-ion batteries has been widely studied and applied. For example, vinylene carbonate is reduced to form a film at the negative electrode to prevent the electrolyte components from being further reduced and decomposed. The simplest and most effective means to improve the electrode interface is to add additives with special functions to the electrolyte; common additives include carbonate additives, phosphites, phosphate additives, organic sulfonates, sulfate additives and organic borate additives. Such additives generally contain special functional groups, and the molecules have higher HOMO (highest occupied molecular orbital) or lower LUMO (lowest unoccupied molecular orbital), so that the molecules are preferentially reduced or oxidized to form a more stable SEI (solid electrolyte interface) film. Similarly, the SEI film also plays a key role in sodium-ion batteries.

[0004] Sulfonate organic substances, such as 1,3-propane sultone, vinyl sulfate, 1,3-propylene sultone, and methylene disulfonate, contain sulfur-oxygen double bonds, which make them easier to be reduced to form SEI films. Such additives play an irreplaceable role in reducing the increase in battery internal resistance and inhibiting gas production, and are widely used in high-voltage lithium-ion batteries and long-cycle life lithium-ion batteries. In the prior art, "Research on the Reaction and Mechanism of Cyclic Sulfonate-Based Electrolyte Additives in Lithium-ion Batteries" points out that 1,3-propane sultone can form a stable SEI film and inhibit battery gas production, but 1,3-propane sultone is a carcinogen and has a high safety risk when used. Summary of the invention

[0005] The present invention provides a sulfonate additive containing a silicon-oxygen bond, an electrolyte and an electrochemical device. The additive is a sulfonate organic compound containing a silicon-oxygen bond. The additive is added to the electrolyte to inhibit the gas production of the battery formation and improve the high-temperature cycle performance of the battery. The additive can also reduce the amount of toxic substances in the electrolyte and reduce the safety risk of the battery.

[0006] The specific technical scheme of the present invention is: A siloxane-containing sulfonate additive, the structural formula of the additive is: Wherein R1 is one or more of a fluoro group and an alkyl group, and R2 is one or more of a phenyl group and an alkyl group.

[0007] The invention provides a sulfonate additive containing a silicon-oxygen bond. The additive is added to an electrolyte to inhibit gas production during battery formation. The additive contains a sulfur-oxygen double bond. The S element in the sulfur-oxygen double bond can be adsorbed on the surface of a transition metal, so that the transition metal is poisoned by the S element and inactivated, thereby forming a stable film structure on the electrode surface. The film structure can inhibit the decomposition of the electrolyte, thereby inhibiting gas production during battery formation. The additive also contains a silicon-oxygen bond. The stability of the silicon-oxygen bond is higher than that of the carbon-oxygen bond. Therefore, during the high-temperature cycle of the battery, the film structure formed by the additive is more stable, which can improve the battery internal resistance during high-temperature cycling and improve the high-temperature cycle performance of the battery. In addition, 1,3-propane sultone in the electrolyte is a high-risk carcinogen, and the silicon-oxygen bond sulfonate additive provided by the invention is safer than 1,3-propane sultone. Adding the silicon-oxygen bond sulfonate additive to the electrolyte can significantly reduce the safety risk of the battery.

[0008] Preferably, the carbon chain length of R2 is 1-20.

[0009] An electrolyte comprises an organic solvent, an electrolyte and an additive 1, wherein the additive 1 comprises the above-mentioned silicon-oxygen bond-containing sulfonate additive.

[0010] The present invention provides an electrolyte, to which an additive one is added, wherein the additive one is a silicon-oxygen bond sulfonate additive. Compared with an electrolyte to which the additive is not added, the electrolyte can inhibit the gas production caused by battery formation, can increase the internal resistance of the battery during high-temperature cycling, and improve the high-temperature cycling performance of the battery.

[0011] Preferably, the mass fraction of the additive 1 is 0.2-0.8%.

[0012] Preferably, the electrolyte further comprises additive 2, which is one or more of dicarbonate additives, phosphite additives, borate additives, sulfate additives, organic salt additives and nitrile additives, and the mass fraction of additive 2 is 0.5-5%.

[0013] Preferably, the second additive includes 1,3-propane sultone and a carbonate additive.

[0014] Preferably, the mass percentage of the 1,3-propane sultone is 0.2-0.8%. The present invention also finds that the siloxane bond sulfonate additive can reduce the amount of 1,3-propane sultone in the electrolyte, and can significantly reduce the amount of 1,3-propane sultone without significantly changing the battery formation gas production effect and high temperature cycle performance. 1,3-propane sultone is a high-risk carcinogen. Reducing the amount of 1,3-propane sultone in the electrolyte can significantly reduce the safety risk of the battery.

[0015] Preferably, the electrolyte is selected from one or two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethanesulfonyl)imide, and the mass fraction of the electrolyte in the electrolyte is 4 to 20%.

[0016] Preferably, the organic solvent is selected from one or more of cyclic carbonates, chain carbonates, ether solvents, alcohol organic solvents, carboxylates and sulfone organic solvents.

[0017] Preferably, the organic solvent is a mixture of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate.

[0018] An electrochemical device contains an electrolyte, and the electrolyte contains the above-mentioned silicon-oxygen bond-containing sulfonate additive.

[0019] Compared with the prior art, this application has the following technical effects: (1) The silicon-oxygen bond-containing sulfonate additive provided by the present invention is added to the electrolyte to inhibit the gas production of the battery formation, and can increase the battery internal resistance during high-temperature cycling, thereby improving the high-temperature cycling performance of the battery; (2) The siloxane bond-containing sulfonate additive provided by the present invention can reduce the amount of 1,3-propane sultone in the electrolyte, and can significantly reduce the amount of 1,3-propane sultone without significantly changing the battery formation gas production effect and high-temperature cycle performance. 1,3-propane sultone is a high-risk carcinogen. Reducing the amount of 1,3-propane sultone in the electrolyte can significantly reduce the safety risk of the battery. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments.

[0021] Embodiment 1: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.5% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.5% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0022] Embodiment 2: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.2% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.8% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0023] Embodiment 3: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.3% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.7% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery made of the above electrolyte, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0024] Embodiment 4: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.4% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.6% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0025] Embodiment 5: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.6% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.4% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0026] Embodiment 6: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.7% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.3% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0027] Embodiment 7: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is trimethylsilylbenzenesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.8% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (0.2% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0028] Embodiment 8: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is triisopropylsilyl trifluoromethanesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.5% of additive 1 (triisopropylsilyl trifluoromethanesulfonate) and additive 2 (0.5% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0029] Embodiment 9: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is tert-butyldimethylsilyl trifluoromethanesulfonate; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.5% of additive 1 (tert-butyldimethylsilyl trifluoromethanesulfonate) and additive 2 (0.5% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0030] Embodiment 10: A siloxane-containing sulfonate additive, wherein the siloxane-containing sulfonate additive is tert-butyl diphenyl silyl trifluoromethanesulfonate; an electrolyte, comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 0.5% of additive one (tert-butyl diphenyl silyl trifluoromethanesulfonate) and additive two (0.5% of 1,3-propane sultone, 5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0031] Comparative Example 1: Compared with Example 1, the electrolyte of Comparative Example 1 does not contain a siloxane-containing sulfonate additive and 1,3-propane sultone; an electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of an electrolyte and a second additive (5% of fluoroethylene carbonate and 2% of vinylene carbonate); a lithium battery, wherein the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0032] Comparative Example 2: Compared with Example 1, in Comparative Example 2, 1,3-propane sultone was not added to the electrolyte; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 1% of additive 1 (trimethylsilylbenzenesulfonate) and additive 2 (5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0033] Comparative Example 3: Compared with Example 8, 1,3-propane sultone was not added to the electrolyte of Comparative Example 3; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 1% of additive 1 (triisopropylsilyl trifluoromethanesulfonate) and additive 2 (5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0034] Comparative Example 4: Compared with Example 9, 1,3-propane sultone was not added to the electrolyte of Comparative Example 4; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of an electrolyte, 1% of a siloxane-containing sulfonate additive (tert-butyldimethylsilyl trifluoromethanesulfonate) and additive II (5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0035] Comparative Example 5: Compared with Example 10, 1,3-propane sultone was not added to the electrolyte of Comparative Example 5; An electrolyte comprising, by mass percentage, an organic solvent (35% of ethylene carbonate, 36% of ethyl methyl carbonate and 10% of diethyl carbonate), 12% of electrolyte, 1% of a sulfonic acid ester additive containing a silicon-oxygen bond (tert-butyl diphenylsilyl trifluoromethanesulfonate) and additive II (5% of fluoroethylene carbonate and 2% of vinylene carbonate); A lithium battery, the battery preparation method comprises the following steps: Step 1: Lithium manganate (mass 4800g), polyvinylidene fluoride (mass 100g) and conductive carbon black (mass 100g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery positive electrode sheets to form positive electrode sheets; Step 2: Graphite (mass 4800g), sodium carboxymethyl cellulose (mass 75g), conductive carbon black (mass 50g) and styrene-butadiene rubber (mass 50g) are homogenized, coated, rolled and die-cut according to the production process of lithium-ion battery negative electrode sheets to form negative electrode sheets; Step 3: According to the lithium-ion battery manufacturing process, the positive electrode sheet and the negative electrode sheet are stacked and assembled into a 12Ah soft-pack battery; Step 4: Prepare the electrolyte according to the above electrolyte formula, and inject the electrolyte into the baked battery (vacuum baking, water content of positive and negative electrodes ≤ 200ppm), the injection coefficient is 4.35g / Ah, and after the injection is completed, the lithium battery is made according to the lithium battery aging, formation, secondary sealing and capacity division processes.

[0036] Test example 1: The battery performance of the soft-pack batteries prepared in the above Examples 1 to 10 and Comparative Examples 1 to 5 was tested. Test items include: high temperature cycle electrochemical internal resistance and battery formation gas production test; The high temperature cycle electrochemical internal resistance is tested by the pulse discharge method, electrochemical internal resistance R = (V1-V2) / I, V1 is the voltage across the battery at 0s of pulse discharge, V2 is the voltage across the battery at 10s of pulse discharge, and I is the pulse discharge current; The gas production of the battery after formation is determined by the water displacement method. The gas production of the battery before and after formation is the volume increment of the battery after formation. The test results are shown in Table 1; Table 1 Battery performance test results Electrochemical internal resistance after 300 cycles (mΩ) Electrochemical internal resistance after 500 cycles (mΩ) Gas production (mL) Example 1 5.85 5.96 9.78 Example 2 6.35 6.63 9.65 Example 3 6.27 6.40 9.25 Example 4 6.17 6.41 9.31 Example 5 5.23 5.47 9.45 Example 6 4.99 5.36 9.51 Example 7 5.56 5.89 9.69 Example 8 5.35 5.67 10.35 Example 9 5.42 5.68 10.21 Example 10 5.65 5.87 10.09 Comparative Example 1 7.41 7.53 14.26 Comparative Example 2 7.23 7.39 13.57 Comparative Example 3 7.11 7.26 12.26 Comparative Example 4 7.58 7.76 13.62 Comparative Example 5 7.04 7.23 12.78 As shown in Table 1, the electrochemical internal resistance of Examples 1 to 10 after 300 high-temperature cycles is 4.99-6.35 mΩ, the electrochemical internal resistance after 500 high-temperature cycles is 5.36-6.63 mΩ, and the gas production after formation is 9.25-10.35 mL. Comparative Example 1 is an electrolyte without adding a siloxane sulfonate additive and 1,3-propane sultone. Compared with Comparative Example 1, Examples 1 to 10 add a siloxane sulfonate additive to the electrolyte to improve the high-temperature cycle performance of the battery and inhibit the formation of The gas production of the battery after completion; in addition, through the results of Examples 1 to 10 and Comparative Examples 2 to 5, the present invention finds that the siloxane-containing sulfonate additive and 1,3-propane sultone have special effects, and the siloxane-containing sulfonate additive can reduce the amount of 1,3-propane sultone in the electrolyte, and can significantly reduce the amount of 1,3-propane sultone without significantly changing the battery cycle performance. 1,3-propane sultone is a high-risk chemical, so reducing its amount can significantly reduce the risk of the battery.

[0037] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A siloxane-containing sulfonate additive, characterized in that: The structural formula of the additive is: , Wherein R1 is one or more of a fluoro group and an alkyl group, and R2 is one or more of a phenyl group and an alkyl group.

2. The siloxane-containing sulfonate additive according to claim 1, characterized in that: The carbon chain length of R2 is 1-20.

3. An electrolyte, characterized in that: It comprises an organic solvent, an electrolyte and an additive one, wherein the additive one comprises the silicon-oxygen bond-containing sulfonate additive as claimed in claim 1.

4. The electrolyte according to claim 3, characterized in that: The mass fraction of the additive 1 is 0.2-0.8%.

5. The electrolyte according to claim 3, characterized in that: The invention also includes additive 2, which includes one or more of carbonate additives, phosphite additives, borate additives, sulfate additives, organic salt additives and nitrile additives, and the mass fraction of additive 2 is 0.5-5%.

6. The electrolyte according to claim 5, characterized in that: The second additive includes 1,3-propane sultone and carbonate additives.

7. The electrolyte according to claim 6, characterized in that: The mass percentage of the 1,3-propane sultone in the electrolyte is 0.2-0.8%.

8. The electrolyte according to claim 3, characterized in that: The electrolyte is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethanesulfonyl)imide, and the mass fraction of the electrolyte in the electrolyte is 4-20%.

9. The electrolyte according to claim 3, characterized in that: The organic solvent is selected from one or more of cyclic carbonates, chain carbonates, ether solvents, alcohol organic solvents, carboxylates and sulfone organic solvents.

10. An electrochemical device, characterized in that: The electrochemical device contains an electrolyte, and the electrolyte contains the silicon-oxygen bond-containing sulfonate additive according to claim 1.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion fast charging battery

    CN114284556A

  • Electrolyte for inhibiting gas production in lithium ion formation and lithium ion secondary battery

    CN114497730A

  • Electrolyte and battery

    CN117790903A

Cited By

  • Electrolyte and battery

    CN120319892A

  • Electrolyte, battery

    CN120319892B

  • Lithium metal battery electrolyte applicable to quick charge and low temperature, battery and preparation method of lithium metal battery electrolyte

    CN121460702A

  • Lithium metal battery electrolyte suitable for fast charging and low temperature, battery and preparation method thereof

    CN121460702B